DETERMINAN TINGKAT KONSUMSI SANTRI KELAS 6 PONDOK MODERN DARUSSALAM GONTOR KAMPUS 2 - Triyawan, Andi; Jani, Reian (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2019)
The one indicator of economic stability in the pondok modern Darussalam Gontor environment is level of consumption. The purpose of this study was to determine the effect of income and lifestyle on the level of consumption of students of class 6 Pondok Modern Darussalam Gontor campus 2. Data analysis method used in this study is a multiple linear regression analysis method. The results of this study indicate that there is a positive relationship between income and consumption, which is the increase in income, the higher the level of consumption. And there is also a positive relationship between lifestyle and consumption, namely the more lifestyle increases, the higher the level of consumption. The results of this study also obtained that there is a very strong relationship between income and lifestyle towards consumption